1998
DOI: 10.1242/jcs.111.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor (PDGF)-induced actin rearrangement is deregulated in cells expressing a mutant Y778F PDGF β-receptor

Abstract: Platelet-derived growth factor-stimulated actin rearrangement and edge ruffle formation have previously been shown to be dependent on activation of phosphatidylinositol 3′-kinase, the activity of which also is important for directed migration of cells. This lipid kinase binds to phosphorylated tyrosine residues Y740 and Y751 in the kinase insert of the human platelet-derived growth factor ss-receptor. We examined the role of two other tyrosine residues in the kinase insert of this receptor, Y775 and Y778, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 18 publications
0
1
0
2
Order By: Relevance
“…Many proteins are involved in PDGFR-mediated signaling, one of them being Nck adaptor protein. It has been shown that Nck can be recruited to bind the PDGFR via its SH2 domain 21 , 33 , 34 . However, the functional role of Nck1 proteins in PDGFR-induced LEC is not well understood.…”
Section: Resultsmentioning
confidence: 99%
“…Many proteins are involved in PDGFR-mediated signaling, one of them being Nck adaptor protein. It has been shown that Nck can be recruited to bind the PDGFR via its SH2 domain 21 , 33 , 34 . However, the functional role of Nck1 proteins in PDGFR-induced LEC is not well understood.…”
Section: Resultsmentioning
confidence: 99%
“…Otro aspecto importante del PDGF-BB es el referente a la modulación ejercida por este factor de crecimiento sobre los cambios morfológicos de las células. Al respecto se ha mostrado que el PDGF-BB induce formación de lamelipodios e incremento de la motilidad en fibroblastos mediado por rearreglos en las fibras de actina, siendo estos procesos dependientes de la quinasa PI3K (Hedberg, et al, 1993;Ruusala et al, 1998). También se ha visto que la expresión del receptor PDGFRβ es necesario para el desarrollo de la cresta neural embrionaria, el desarrollo y diferenciación astrocitaria y la morfogénesis y plasticidad de espinas dendríticas (Svitkina et al, 2010;Funa y Sasahara, 2014) Igualmente se ha mostrado que factores de crecimiento como el PDGF-BB y el VEGF inducen la activación de la proteína RhoA en células endoteliales, durante el proceso de angiogénesis (Nobes et al, 1995;van Nieuw et al, 2003).…”
Section: Efectos Del Pdgf-bb Asociados a La Morfología Celular Y Acti...unclassified
“…Además, se ha demostrado que tanto Rac1 como RhoA de la familia GTPasas de Ras median la formación de procesos en cultivos de astrocitos hipocampales de rata (Kalman et al, 1999), sugiriendo la importancia de estas proteínas para la morfología astrocitaria. Por otra parte, se ha demostrado que el PDGF-BB puede activar mecanismos implicados en la modificación del citoesqueleto y la migración celular, incluyendo el desarrollo del SNC (Hedberg, et al, 1993;Ruusala et al, 1998;Zohrabian et al, 2009;Funa y Sasahara, 2014). Estos procesos pueden ocurrir por la movilización del fosfatidil inositol 3,4,5, y la consecuente activación de la proteína rac GTPasa de la familia Rho, que está implicada en la modificación del citoesqueleto de actina y cambios morfológicos (Nobes et al, 1995;Li et al, 2010), lo que sugiere la importancia del PDGF-BB en la regulación morfológica frente al insulto por rotenona.…”
Section: Efectos Del Pdgf-bb En La Viabilidad Y Activación Astrocitariaunclassified